The Effect of Non Performing Financing and on Financing of Natural Uncertainty Contract (NUC) with Third Party Fund (DPK) as a Moderating Variable - Utami, Tri; Angraini, Dila; Annisa, Dea; Irawati, Wiwit (Universitas Dian Nuswantoro Semarang, 2021)
This type of research is quantitative associative and the data used is the annual data on the financial statements of Islamic Commercial Banks registered with the Financial Services Authority for the 2015-2018 period, totalling 14 BUS. The sample is determined using a purposive sampling method. The number of Islamic Commercial Banks studied was 8 with a research period of 4 years to obtain 32 samples. This study uses the Multiple Linear Regression method, using the help of the EViews 9 program. From the results of hypothesis testing, it is found that the variable financing problems and SBIS have a joint effect on NUC. However, partially problematic financing has no effect on NUC and SBIS has a positive effect on NUC. With TPF as a moderating variable, the test results using the Moderated Regression Analysis technique show that TPF does not moderate the effect of non-performing financing (NPF) on NUC but TPF can moderate the effect of the SBIS variable on NUC. Keywords: Natural Uncertainty Contract (NUC) Contract Financing, Third-Party Funds (DPK), Non-Performing Financing, Certificate of Bank Indonesia Syariah (SBIS)